A GC-MS Based Metabolic Profiling of Probiotic Lactic Acid Bacteria Isolated from Traditional Food Products - Aditya Chaudhary; Khushbu Verma; Baljeet Singh Saharan (Journal of Pure and Applied Microbiology, 2020)
A GC-MS based metabolic profiling was carried out to study metabolic differences of lactic acid bacteria isolated from different food sources. Metabolic fingerprinting is a non-targeted procedure where all detectable peaks are considered to establish sample classification. A total of 40 compounds were identified as major metabolites contributing to the difference among five different probiotic lactic acid bacteria. Some of the metabolites identified in this study have been reported as a defrosting agent, antioxidant, flavour agent, antimicrobial, natural food additive, anti-inflammatory, anti-sleep disorder agent and anti-cancer agents. These results suggest that GC-MS based metabolomic analysis is a useful tool to facilitate future investigations into the characterization of probiotic lactic acid bacteria.